2018
DOI: 10.1016/j.nmni.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

First report of colistin resistance among carbapenem-resistant Acinetobacter baumannii isolates recovered from hospitalized patients in Egypt

Abstract: Acinetobacter baumannii is an opportunistic pathogen that poses an increasing threat in the health-care community. Colistin is one of the promising options for treatment of multidrug-resistant A. baumannii. The current study investigated the emergence of colistin resistance among carbapenem-resistant strains of A. baumannii in Egypt. It involved identification of clinically recovered A. baumannii isolates using the VITEK-2 system, and screening of their antimicrobial susceptibilities using broth microdilution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 39 publications
(45 reference statements)
5
30
1
Order By: Relevance
“…A. baumannii is now regarded as one of the most difficult nosocomial-acquired pathogens to treat and control, characterized by a worryingly increasing rate of colistin resistance, observed worldwide [7,23,24]. In our study, we propose that the incidence of MDR A. baumannii is very high in Egypt.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A. baumannii is now regarded as one of the most difficult nosocomial-acquired pathogens to treat and control, characterized by a worryingly increasing rate of colistin resistance, observed worldwide [7,23,24]. In our study, we propose that the incidence of MDR A. baumannii is very high in Egypt.…”
Section: Discussionmentioning
confidence: 76%
“…In our study, we propose that the incidence of MDR A. baumannii is very high in Egypt. However, Abdulzahra and his colleagues demonstrated that only two A. baumannii isolates were colistin-resistant [24].…”
Section: Discussionmentioning
confidence: 99%
“…In a burn ward in Iran, 96.92% of clinical isolates of A. baumannii were shown to be resistant to meropenem and imipenem, with CRAB isolates carrying the oxacillinase determinants of bla OXA-23 accounting for 74.6%, suggesting that high-level CRAB with bla OXA-23 in burn patients is a reason for A. baumannii resistance to carbapenems [ 33 ]. Abdulzahra revealed that 80% of A. baumannii isolates carry bla OXA-23 , which implies that it is a crucial healthcare concern in Egypt that necessitates strict interventions to eliminate such infections [ 34 ]. Lowo et al collected 141 A. baumannii strains from two tertiary academic hospitals (A and B) in South Africa; the results showed that these clinical isolates carried the bla OXA-23 gene at a rate of 96% (69/72) in hospital A versus 91% (63/69) in hospital B, implying that greater infection control and prevention strategies need to be developed [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present MDR strains, tigecycline was an effective therapeutic agent with a susceptibility level of >95%, being considerably greater than that estimated in various local studies (20–70%) [ 2 , 3 ]. Although half of the isolates were resistant to aminoglycoside, studies in our region have reported different levels of gentamicin and amikacin resistance (25–96%) [ 4 ], while increased aminoglycoside resistance has been reported in studies in China and Egypt [ 17 , 18 ]. Furthermore, very high fluoroquinolone resistance levels were observed in our isolates, concurrent with previous reports from other GCC countries and Turkey [ 4 , 19 ].…”
Section: Discussionmentioning
confidence: 94%